Neuroprotective Role of GLP-1 Analog for Retinal Ganglion Cells via PINK1/Parkin-Mediated Mitophagy in Diabetic Retinopathy - Zhou, Huan-ran; Ma, Xue-fei; Lin, Wen-jian; Hao, Ming; Yu, Xin-yang; Li, Hong-xue; Xu, Cheng-ye; Kuang, Hong-yu (Frontiers in Pharmacology, 2021)
GLP-1 analogs are widely used to treat patients with type 2 diabetes in recent years. Studies have found that GLP-1 analogs have multiple organ benefits. However, the role of GLP-1 analog in diabetic retinopathy (DR), a common complication of diabetes mellitus (DM), remains controversial. Retinal ganglion cells (RGCs) are the only afferent neurons responsible for transmitting visual information to visual center and are vulnerable in the early stage of DR. Protection of RGC is vital for visual function. The incretin glucagon-like peptide-1 (GLP-1), which is secreted by L-cells after food ingestion, could lower blood glucose level through stimulating the release of insulin. In the present study, we evaluated the effects of GLP-1 analog on RGCs both in vitro and in vivo. We established diabetic rat models in vivo and applied RGC-5 cell line in vitro. The results showed that in high glucose condition, GLP-1 analog alleviated the damage of RGCs. In addition, GLP-1 analog prevented mitophagy through PINK1/Parkin pathway. Here we demonstrated the neuroprotective effect of GLP-1 analog, which may be beneficial for retinal function, and we further elucidated a novel mechanism in GLP-1 analog-regulated protection of retina. These findings may expand the multi-organ benefits of GLP-1 analogs and provide new insights for the prevention of DR.